Macronutrients and sugar content in foods and beverages from three selected zones in Peninsular Malaysia - Rosmawati Dora,; Hasnah Haron,; Suzana Shahar,; Chong, Ching Phang; Muhamad Fikri Mohd Fauzi,; Mohd Fairulnizal Md Noh, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was conducted to determine the content of macronutrients and sugar in 30 types of food selected from three zones in Peninsular Malaysia. The food samples consisted of 14 types of processed foods and beverages, 8 types of fruits and 10 types ready to eat food. Each type of food and drink were purchased from selected restaurants, stores and supermarkets from three different zones which were North zone (Perak), Central zone (Selangor) and South Zone (Johor). Methods used for proximate analysis were based on the standard methods of AOAC (1997) while the total carbohydrate was calculated by difference method. Total calories were calculated using Atwater method. Total sugar content were analysed using high performace liquid chromatography (HPLC). Dietary fibre contents were determined by using a combination of enzyme-gravimetric methods (AOAC 985.29 and AACC 32-05). The results showed that peanut butter has the highest value of fat (44.75 ± 7.59 g/100 g), total calorie (611 ± 38 kcal /100 g) and dietary fibre contents (8.07 ± 0.98 g/100 g). Highest protein content (21.98 ± 2.57 g/100 g) was found in low-fat milk powder. The highest carbohydrate (97.48 ± 1.47 g/100 g) and total sugar (86.7 ± 2.9 g/100 g) contents were found in palm sugar. The results of this study will update and add up to the data for the Malaysian Food Composition Table and can provide useful information in choosing healthy foods based on the nutrient contents of the food.